(untitled) (Journal of Human Sciences, 2022)
This research aims to clarify the judgments related to the rules of protecting the privacy of homes By considering home violations as faults, the Islamic law (sharia) recognizes the sanctity of homes because homes protect the privacy of its inhabitants, so it is forbidden to violate them in any circumstance to see what is inside these homes Here, the judgment differs according to the situation of the intruder and the occupant and the posture of each one It is forbidden for anyone to enter someone’s home without permission either the occupier is a tenant or owner or if the intruder is a relative or not To clarify this issue, we shall view the judgement of each one of the four (schools) of Islam, weigh and analyze them and bring along our comments to be aware of each jurisprudential opinion of these (schools) with regard to the Islamic law dealing with this research.